(untitled) (African Disability Rights Yearbook, 2024)
Internal displacement occurs when persons involuntarily flee from their homes or places of habitual residence but stay within their State’s borders to avoid the destructive and harmful effects of natural or man-made disasters. This is a recurring human rights issue in South Africa, with internal displacements occurring frequently in various parts of the country. However, this article focused on the severe floods that occurred in KwaZulu-Natal (KZN) in April and May 2022, which resulted in the internal displacement of 40 000 persons who required urgent intervention and humanitarian support from the State. Due to the trauma and harm caused by displacement, internally displaced persons are generally vulnerable to human rights violations; and children with disabilities are already vulnerable. Therefore, internally displaced children with disabilities require special protection from the State as they are doubly vulnerable and at risk of human rights violations. Thus, this article aimed to evaluate the State’s protection of the right to a standard of living of internally displaced children with disabilities in KZN against benchmark standards to determine if the State’s response adequately protected the right to a standard of living of these children. The article developed benchmark standards through doctrinal research that relied on the Convention on the Rights of the Child, the Convention on the Rights of Persons with Disabilities, the African Charter on the Rights and Welfare of the Child, the South African Constitution and Children’s Act and drew best practices from the Kampala Convention and the Guiding Principles on Internal Displacement; as well as various secondary legal sources and media articles related to the KZN floods. For the adequate protection of a standard of living for internally displaced children with disabilities, a common thread of respect for dignity, non-discrimination, and the provision of special measures to meet the needs of shelter, healthcare and education during and after displacement for children with disabilities was found through both the international treaties and domestic laws.